The Effect of Humor as a Stress Management for Nurses Working in Hospital: Systematic review - Rany Agustin Wulandari; Hamidah Retno Wardani (Universitas Bondowoso, 2022)
Introduction : Nurses are one of the health workers who provide health services who encounter various conditions that can cause stress. Nurses who feel the stress certainly have an impact on the quality of health service that they are giving, therefore the stress management to overcome the stress is needed. One of the stress management that is cheap and accessible for nurses anywhere and anytime is humor. Method: This study uses a systematic review method. Result: Humor is a way that can change the psychological condition of individuals. Ways of this humor therapy is smiling and laughing. Nurses can smile and laugh by reading comics, joking, watching comedy filmsand or can be in the form of a fictional story told by a friend who is considered funny, and so on. In this study, the nurses believed that humour provides an opportunity for change. In relation to this, the results showed that the consequences of humour can range from revival to exhaustion. In addition to enabling mental rest, humour helps change patients’ perspectives regarding their health condition. Conclusion: Stress conditions experienced by nurses arise due to workload and so on. This will have an impact on nursing care services that will be provided to patients in the hospital. Humor is one of the most effective stress management tools to reduce stress. Humor that nurses do is just enough to smile and laugh, of course this method is very easy to do and does not require expensive costs.